On Mixed Flow Turbines for Automotive Turbocharger Applications - Bernhardt Lüddecke; Dietmar Filsinger; Jan Ehrhard (International Journal of Rotating Machinery)
Due to increased demands for improved fuel economy of passenger cars, low-end and part-load performance is of key importance for the design of automotive turbocharger turbines. In an automotive drive cycle, a turbine which can extract more energy at high pressure ratios and lower rotational speeds is desirable. In the literature it is typically found that radial turbines provide peak efficiency at speed ratios of 0.7, but at high pressure ratios and low rotational speeds the blade speed ratio will be low and the rotor will experience high values of positive incidence at the inlet. Based on fundamental considerations, it is shown that mixed flow turbines offer substantial advantages for such applications. Moreover, to prove these considerations an experimental assessment of mixed flow turbine efficiency and optimal blade speed ratio is presented. This has been achieved using a new semi-unsteady measurement approach. Finally, evidence of the benefits of mixed flow turbine behaviour in engine operation is given. Regarding turbocharged engine simulation, the benefit of wide-ranging turbine map measurement data as well as the need for reasonable turbine map extrapolation is illustrated.